Elektromobillərin xidmət infrastrukturunun təşkili xüsusiyyətləri - Məmmədli, İltifat; Babayev, Mehralı; Ələsgərov, Elvin; Səidi, Şaiq (My University, 2024)
The main objective of the dissertation is to provide general information about the systems that organize electric vehicles and their design and to provide a framework for the study of electric vehicles in the automotive market by developing models of the adoption of relevant technologies. The aim is to draw up an action plan for the development and organization of a number of services for a car service company designed for electric and hybrid vehicles that also use a high-voltage lithium-type battery as an energy element for movement.
Features of the organization of the service infrastructure of electric vehicles
Keywords: Electric vehicle maintenance